FORMING OF STRATEGICALLY-ORIENTED PORTFOLIO OF INNOVATIVE PROJECTS FOR ELECTRIC POWER EQUIPMENT MODERNIZATION - Олег Анатолійович САЧЕНКО (Вісник Національного технічного університету «ХПÌ». Серія: Стратегічне управління, управління портфелями, програмами та проектами, 2017)
The evaluation of the seven basic portfolio management procedures was done according to the international standard ISO 21504 and it was recognized for greater efficiency to do the detailed analysis of two procedures: 1) the verification of the correspondence the portfolio to strategic objectives of the power company; 2) the balancing and the optimizing for portfolio. Also, it is proposed to apply in the portfolio management process the competent person (portfolio manager) for the security of continuous strategic coordination for the portfolio of innovative projects in power company for the balancing and controlling the portfolio. Recommendations for implementation of the strategically oriented portfolio of innovative projects for equipment modernization of the power company are performed too.